2019
DOI: 10.3389/fendo.2019.00412
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Metabolic Control in Patients With Type 2 Diabetes Attending Dasman Diabetes Institute, Kuwait

Abstract: Purpose: To evaluate metabolic control in patients with type 2 diabetes at Dasman Diabetes Institute (DDI, Kuwait), a specialist diabetes clinic and research center, and to investigate its association with patient demographics and clinical characteristics. Methods: Data from 963 patients with type 2 diabetes were retrospectively collected from the Knowledge Based Health Records maintained at DDI for patients who attended DDI during 2011–2014. The collected data included patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…In this study a significant relationship was reported between longer duration of diabetes and HBA1c>7% prevalence. The prevalence of HBA1c>7% in Qaddoumi's study in 2019 among Kuwaiti diabetic patients with a history of equal or over 10 years of diabetes was 15% higher than in other patients [ 36 ]. Various studies have shown that the risk of developing diabetes-induced complications will increase when its duration increases [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study a significant relationship was reported between longer duration of diabetes and HBA1c>7% prevalence. The prevalence of HBA1c>7% in Qaddoumi's study in 2019 among Kuwaiti diabetic patients with a history of equal or over 10 years of diabetes was 15% higher than in other patients [ 36 ]. Various studies have shown that the risk of developing diabetes-induced complications will increase when its duration increases [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30% of patients attending a specialist diabetes medical and research center in Kuwait between 2011 and 2014 had an HbA1c <7% [18]. A study analyzing data from the Kuwait Diabetes Register reported that only 26% of Kuwaiti diabetic patients had an HbA1c <7% in 2012 [19], while in Kuwait in 2010 glycemic control was reportedly between 19% [20,21] and 21% [22].…”
Section: Discussionmentioning
confidence: 99%
“…For categorical variables, we conducted chisquare test or Fisher's exact test to indicate whether presence of conditions differed across disease groups. Based on the analyses, we selected variables with the p-values less than 0.05 to predict COVID-19 severity by a nominal logistic regression with adjustments to age and gender [8][9][10][11][12] . All statistical analyses were carried using R version 3.6.2.…”
Section: Discussionmentioning
confidence: 99%